The Facial approximation of the controversial skull attributed to Wolfgang Amadeus Mozart (1756–1791) - Moraes, Cicero; Šindelář, Jiří; Habicht, Michael E.; Sineo, Luca; Beaini, Thiago; Varotto, Elena; Galassi, Francesco Maria (Anthropological Review, 2025)
Wolfgang Amadeus Mozart (1756–1791) is considered as one of the greatest composers of the Classical Period of music (ca. 1750–1820). Gifted with an unparalleled precocity, which allowed him to play and compose at the highest levels from a very young age, he continued his studies until the end of his life. Despite his prominent status, he was buried in a collective grave and years later his skull was supposedly recovered, reaching the present day surrounded by an atmosphere of mystery and controversy. This study, using a free, open-source, multiplatform software and the available published material, independently seeks to approximate the face of this skull and compare it with previous publications and portraits painted during the composer’s lifetime.